Pengaruh Reinventing Policy dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Bumi dan Bangunan Sektor Perdesaan & Perkotaan (PBB-P2) Kota Bandung: The Effect Of Reinventing Policy and Tax Penalties In Paying Land And Building Tax Of Rural And Urban Sectors (PBB-P2) In Bandung City - Fitriani, Nisa; Kusumastuti, Endah Dwi (Indonesian Accounting Research Journal, 2025)
This study aims to determine the effect of Reinventing Policy and Tax Penalties in paying PBB-P2 in Bandung. This research is prompted by the decrease in the collection of PBB-P2 and the elevated nominal value of PBB-P2 receivables annually. Despite the annual increase in the number of taxpayers in Bandung, this growth has not corresponded with improved tax compliance.The research method used is descriptive quantitative. The sample was determined based on the Accidental Sampling method with a specified sample size of 100 respondents. This research uses primary data collection methods in the form of questionnaires as research instruments, which are structured based on the Likert scale, and the data is processed using the SmartPLS 4 application version 4.1.0.9. The results of this study indicate that Reinventing Policy and Tax Penalties simultaneously have a significant impact on Taxpayer Compliance. The R-Square value of 0.774 shows that Reinventing Policy and Tax Penalties contribute to Taxpayer Compliance by 77.4%, while the remaining 22.6% is influenced by other variables